Changes to agility running technique during reactive performance conditions - Wheeler, K. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to examine agility running technique during planned and reactive conditions specific to rugby union. The variation to running technique of 8 highly trained rugby union players was compared between agility conditions (pre-planned and reactive) and also agility performance speeds (fast, moderate and slow). The development of lateral movement during the side-step was less (planned = 0.69 ±0.43 m/s vs. reactive = 0.25 ±0.42 m/s, p <.001) with a decision-making element. Fast performances exhibited greater lateral movement during the side-step (0.52 ±0.34 m/s) compared to moderate (0.20 ±0.37 m/s, p = .034) and slow (-0.08 ±0.31 m/s, p <.001) for reactive conditions. The differences between planned and reactive conditions highlight the need to incorporate decision-making in rugby union agility programs.